Get Beyond Limits: From Colloidal Tectonics Concept to the Engineering of Eco-Friendly Catalytic Systems - Leclercq, Loïc (Frontiers in Chemistry, 2018)
The interactions between two or more molecules or colloidal particles can be used to obtain a variety of self-assembled systems called supramolecules or supracolloids. There is a clear, but neglected, convergence between these two fields. Indeed, the packing of molecules into colloidal or supracolloidal particles emerges as a smart solution to build an infinite variety of reversible systems with predictable properties. In this respect, the molecular building blocks are called “tectons” whereas “colloidal tectonics” describes the spontaneous formation of (supra)colloidal structures using tectonic subunits. As a consequence, a bottom-up edification is allowed from tectons into (supra)colloidal particles with higher degrees of organization. These (supra)colloidal systems can be very useful to obtain catalysts with tunable amphiphilic properties. In this perspective, an overview of colloidal tectonics concept is presented as well as its use for the design of new, smart and flexible catalytic systems. Finally, the advantages of these catalytic devices are discussed and the perspective of future developments is addressed especially in the context of “green chemistry”.